Targeted Therapeutics in Melanoma - Gajewski, Thomas F.; Hodi, F. Stephen (Current Clinical Oncology,, 2012)
Melanoma is an increasingly important public health problem. Although the cause of most malignant melanomas - over-exposure to ultraviolet light - is well known, effective treatment has remained challenging. The past several years have been marked by extraordinary developments in melanoma treatment in the arena of targeted therapeutics. This book describes these ground-breaking discoveries and their implications for clinical use. As melanoma biology is increasingly understood, so the development of targeted therapies for this disease is spurred ahead. This book covers both established signal transduction inhibitors and the fascinating emerging realm of molecularly-guided immunotherapies. This benchmark book provides the most up-to-date information on the new breed of melanoma therapies. Composed of the works of major researchers and clinicians, this book offers new insights, novel approaches, and promising data for effective treatment planning. Illuminating the latest advances in the field, it is a solid resource for clinical oncologists, translational scientists, and basic cancer researchers.